Classification of technologies for organizing youth leisure activities (Journal of Educational Sciences, 2023)
The article deals with the problems of systematization of youth leisure technologies, the development of their classification. The object of research is the organization of youth free time and leisure. The subject of the study is the classification of technologies for organizing youth leisure. The purpose is to substantiate and develop a classification of technologies as a method of systematization of cultural and leisure work with young people based on a set of different criteria. The objectives of the article are to determine the degree of research of the problem in the scientific literature; to identify technologies used in practical work in the organization of free time activities of young people; to theoretically substantiate and develop a classification of technologies for organizing youth leisure; to group the technologies used in accordance with their essential characteristics. The solution of the tasks was solved using general theoretical methods: analysis of scientific literature; synthesis of the obtained data; collection of information, analysis and generalization of best practices in the organization of cultural and leisure activities, technologies used in practice; classification – the distribution of technologies into groups according to certain characteristics. As a result, the author concluded that there is a wide range of technologies used in practice, on the one side, and the lack of validity and development of their classification, on the other. The variety of technologies used requires their classification, grouping and classes according to certain criteria. The author analyzes various approaches to the grouping of technologies used in the cultural and leisure sphere. Thus, as features of the classification of technologies, the following are distinguished: the nature of the interaction of subjects of cultural and leisure activities (authoritarian, personality-oriented, humane-personal, cooperation); the ratio of applied traditional and innovative methods of work (traditional, alternative, innovative technologies); age composition of participants (technologies for organizing leisure activities for children, teenagers, youth, and people of mature age). The author substantiates the classification of technologies for organizing of cultural and leisure activities according to the following criteria: technologies for organizing youth leisure on a functional basis; technologies for organizing youth leisure according to the methods of work used; technologies for organizing youth leisure in terms of content. Theoretical and practical applicability of the article: the results obtained allow us to expand knowledge about the technologies used in the organization of youth free time and leisure, to substantiate and classify them in order to select an alternative, ensure the effectiveness and efficiency of work.Key words: youth leisure activities, technology for organizing youth free time and leisure activities, classificat ion of technologies of organization of youth leisure.